Stakeholder engagement in waste management: understanding the process and its impact on accountability - Zakaria, Zarina (2011)
This thesis examines the operationalisation of stakeholder engagement process in sustainable waste management setting. The study aims to establish role of stakeholder power in the prioritisation process and add to empirical understanding of the way engagement affect accountability, which evaluates both the `process', and the `outcome' of engagement. This research is based on a three mini cases of local government authorities, which involve in-depth interviews, observations and document analysis. A broader insights of the engagement process from several stakeholder groups, namely the residents, NGOs, councillors and private waste contractors, are considered and compared with managerial views, and several aspects of stakeholder engagement practices are analysed, including the mechanisms used as well as the challenges faced by the LGAs in engaging. In addition, the intentions behind engagement undertakings are analysed and evaluation of the effectiveness of stakeholder engagement practices are made. Drawing on stakeholder theory, the role of power is explored as a stakeholder attribute in determining salience and in the engagement process. Insights from the interviewees are analysed in relation to the extent of participation and perceived level of power held which are then used to map the extent of their involvement on the ladder of engagement.